SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT NELAYAN ANDREW KURNIAWAN NIM : 09.01.53.0134 11323 PROGRAM STUDI S1 TEKNIK INFORMATIKA FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS STIKUBANK SEMARANG 2014 (Information Technology and Telematics, 2014)
ABSTRACT Analysis of the new system of planning on lending decision support system includes an evaluation of the fishermen of the proposed system , object-oriented design ( OOD ) and Entity Relationship Diagram ( ERD ) , a database specification , design and implementation plan process . Based on the analysis and research on the author , it can be concluded that the decision-making process is made with modeling that takes into account the various factors that serve as models of assessment. Decision-making process based on the assessment of data fisherman who becomes the object of this Department of Fisheries and Marine Semarang . Parameters include assessment of fish production data and guarantees that will be used as benchmarks . From these data it can be done for the feasibility assessment process decisions will be made by the system are then used to support the decision by the Head of Department.Keywords : Decision Support System Lending Fishermen , PHP , Mysql .